Analisis Kepuasan Wisatawan Terkait Destinasi Wisata di Pantai Selong Belanak - Ayu Sukmawati; Rabiatul Adawiyah; Anisya Nurtalitha; Ahmad Safoan; Devi Purnama Sari; Baiq Latifa Pebriani; Dimas Merdeka Sudiharto; Aulia Adianingsih; M. Roihan Al-Munawar; Dede Minggra Mujiburahman; Eko Pradjoko (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Mataram, 2023)
Selong Belanak Beach is one of the beaches that is quite famous, especially for its beauty and beauty. Its strategic location, famous history, public facilities and extras, make Selong Belanak beach a very attractive location for tourists. But one of the important roles for these tourist destinations is the cleanliness of the beach itself, providing comfort for tourists. Direct observation study and descriptive cross-sectional study with a random survey of 54 local and foreign tourists about the cleanliness of Selong Belanak beach. Through a survey, we collect tourists' evaluations of the current sanitation of public facilities (toilets, parking and rest areas), additional facilities (restaurants, gift shops and street vendors), and the condition of MCK facilities (trash bins) at Selong Belanak Beach, giving a score very satisfied, satisfied, moderately satisfied, dissatisfied, very dissatisfied. Through direct observation we saw physical objects around the environment such as geography and the facilities available at Selong Belanak beach which were collected through interviews with local informants. Respondents as a whole showed a positive response